Experimental characterization of the axial behavior of traditional masonry wall metal tie connections in cavity walls. (10th January 2021) - Arslan, Onur; Messali, Francesco; Smyrou, Eleni; Bal, İhsan E. and Rots, Jan G.
Highlights: Assessing the seismic response of the wall tie connections in cavity walls. Results obtained in terms of average force-displacement curves/failure mechanisms. Additional characterization tests on the materials performed. Embedment length and geometry of tie influences the capacity of the connection. Precompression level and loading rate does not have a significant influence. Abstract: In recent years, the number of human-induced earthquakes in Groningen, a large gas field in the north of the Netherlands, has increased. The majority of the buildings are built by using unreinforced masonry (URM), most of which consists of cavity (i.e. two-leaf) walls, and were not designed to withstand earthquakes. Efforts to define, test and standardize the metal ties, which do play an important role, are valuable also from the wider construction industry point of view. The presented study exhibits findings on the behavior of the metal tie connections between the masonry leaves often used in Dutch construction practice, but also elsewhere around the world. An experimental campaign has been carried out at Delft University of Technology to provide a complete characterization of the axial behavior of traditional connections in cavity walls. A large number of variations was considered in this research: two embedment lengths, four pre-compression levels, two different tie geometries, and five different testing protocols, including monotonic and cyclic loading. The experimental results showed that the capacity of the connection was strongly influenced by the embedment length and the geometry of the tie, whereas the applied pre-compression and the loading rate did not have a significant influence.